After Life : An Ethnographic Novel - Hecht, Tobias, 1964- (Book collections on Project MUSE., 2006)
Ethnographic novel based on research in Northeast Brazil, centered around interviews with a 17-year old transgendered youth who subsisted on the street for eight years through begging and prostitution.